Impact of gender and age on inner diameter of arteries forming circle of Willis assessed by multidetector CT - Sharma, Prakash; Lalchan, Subita; KC, Subhash; Gyawali, Merina; Kushwaha, Niraj (Journal of Brain and Spine Foundation Nepal, 2021)
Introduction: The circle of Willis (CoW), which is located at the base of the brain is the most important anastomosis between the internal carotid and vertebral system. It is the main distributor of blood to the brain. Methods: CT head and CT angiography were performed using standard scan parameters. Only the tests with normal radiological reports and appropriate technical standards were included in the study. Component of circle of Willis: Anterior cerebral artery (ACA), Middle cerebral artery (MCA), Anterior communicating artery (Acom), Posterior Communicating artery (PCom), Basilar artery (BA) and Posterior cerebral artery (PCA) were identified and their internal diameter were measured. Results: Basilar artery was the artery with largest internal diameter with mean diameter of 2.5 ±0.52 mm. Men had significantly larger arterial sizes than women in all of the intracranial arteries examined except right PCom, Left PCom and right MCA. Right ACA had significantly larger internal diameter in <40 years’ age group. BA, left PCA, Bilateral PCom and MCA showed larger diameter in age group ≥40 years. Conclusion: Men had significantly larger arterial sizes than women in all of the intracranial arteries examined except right PCom, Left PCom and right MCA.